PENGARUH SERVICE PERFORMANCE DAN RELATIONSHIP MARKETING TERHADAP LOYALITAS KONSUMEN - Agus Budi Purwanto (STIE Pelita Nusantara Semarang, 2015)
This research is motivated by business competition in the smartphone market where smartphones are growing very rapidly. This study aims to determine the effect of service performance and relationship marketing on customer loyalty. Specifically, this study aims to provide solutions to increase smartphone sales amid increasingly fierce competition. The variables in this study consists of three variables: service performance and relationship marketing becomes the independent variable while loyalty becomes the dependent variable. Data collection techniques by spreading questionnaire study on smartphone users in the city of Semarang are arranged systematically with few options easy to understand answer. Distribution of questionnaires carried out in the period from January to March 2015, with the sample for a total of 90 people. Then the data collected through a questionnaire to test the validity and reliability. Hypothesis testing using multiple regression analysis. To obtain regression results BLUES (best linear Unbiased estimated), previously performed classical assumption. The result of the research proves that there is positive direct influence between service performance and relationship marketing to customer loyality.